Field Theory in Particle Physics, Volume 1 - Wit, B. de; Smith, J (North-Holland Personal Library, 2012)
``Field Theory in Particle Physics'' is an introduction to the use ofrelativistic field theory in particle physics. The authors explain the principalconcepts of perturbative field theory and demonstrate their application inpractical situations. The material presented in this book has been testedextensively in courses and the book is written in a lucid and engaging style.Many interesting problems are included at the end of each chapter, both to testthe understanding of the subject matter and to further amplify the ideas in thetext. The authors have taken great care to make their presentation asself-contained as possible by adding several appendices.